Managing unanchored, heterogeneous expectations and liquidity traps - Cars H. Hommes; Joep Lustenhouwer (Bamberg University, Bamberg Economic Research Group (BERG), 2017)
We study the possibility of (almost) self-fulfilling waves of pessimism and selfreinforcing liquidity traps in a New Keynesian model with heterogeneous expectations. We explicitly focus on the "anchoring" of expectations that is modeled as the range of deviations from the central bank targets (and from the rational expectation equilibrium) that agents are willing to consider. We find that when the zero lower bound on the nominal interest rate is not binding, aggressive monetary policy can prevent waves of pessimism and exclude near unit root dynamics, even when expectations are unanchored. However, as shocks bring the economy to a situation with a binding zero lower bound, there is a danger of a long lasting self-reinforcing liquidity trap that arises because of the existence of multiple steady states. It turns out that in a model where the anchoring of expectations evolves endogenously, the anchoring of expectations at the time the bad shocks hit is crucial in determining whether the economy can recover from the liquidity trap. Furthermore, a higher inflation target reduces the probability that self-reinforcing liquidity traps arise.
Keywords: E52; E32; C62; 330; Interest Rate Rules; Liquidity Traps; Heterogeneous Expectations; Bounded Rationality; Multiple Steady States